Benefits of Hypnotherapy on Interest in Learning for Grade VI Elementary School Students - Lilis Nihayah; Wahyu Retnani (Psikologia : Jurnal Psikologi, 2011)
Interest in learning in a student plays an important role that has an impact on behavior and attitudes. While the role of interest in the learning process is to concentrate thoughts and create its own pleasure. Hypnotherapy is one method that can be used as a means of reprogramming the subconscious mind, in order to provide positive learning suggestions. The purpose of this hypnotherapy is to improve the learning of sixth graders at SDN Tenggulunan. The hypnotherapy process itself is carried out with various techniques in order to reach the subconscious mind. Because the subconscious mind has an influence as much as 88% compared to the conscious 12%. Interest has elements of cognitive, emotional, effective. The data obtained before in the field is the very broad benefits of hypnotherapy, then when in the field the process of implementing hypnotherapy is carried out several times so that the suggestions given can have the expected results. After implementation in the field, the results of changes are not only based on academic values, but include emotions, effectiveness. So that when the implementation of hypnotherapy is successful, in the subconscious mind, how to solve an obstacle.